2016
DOI: 10.1136/heartjnl-2016-309968
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of paramedic treatment of regular supraventricular tachycardia: a randomised controlled trial

Abstract: NCT02216240.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…[27] Honarbakhsh et al in a randomized controlled trial revealed that there was a 98% correlation between the paramedics’ ECG diagnosis of supraventricular tachycardia and that of 2 electrophysiologists. [28] ECG interpretation skills were also examined among Polish EMS providers. The results of the Competition in Medical Rescue Krakow 2014, which consisted of interpretation of 5 different records depicting STEMI, atrial fibrillation, supraventricular tachycardia, third degree atrioventricular block were later analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Honarbakhsh et al in a randomized controlled trial revealed that there was a 98% correlation between the paramedics’ ECG diagnosis of supraventricular tachycardia and that of 2 electrophysiologists. [28] ECG interpretation skills were also examined among Polish EMS providers. The results of the Competition in Medical Rescue Krakow 2014, which consisted of interpretation of 5 different records depicting STEMI, atrial fibrillation, supraventricular tachycardia, third degree atrioventricular block were later analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The current ERC guidelines [6] recommend the treatment in narrow and broad complex tachycardia in stable and unstable patients. SVT is a common cause of acute hospital presentations [7].…”
Section: Discussionmentioning
confidence: 99%
“…Honarbakhsh et al [7] compared paramedicwith the hospital-delivered treatment of acute SVT with adenosine. They revealed that patients with SVT could be effectively and safely treated by paramedics with the use of adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to reduce the burden of SVTs on emergency departments have included examining paramedic-led adenosine administration in the community when the patient has a narrow complex tachycardia without a history of structural or ischaemic heart disease. [ 52 ] Successful adenosine cardioversion at the scene of presentation allows immediate discharge of certain patients with follow-up arranged by the primary care physician. In this study, 81% of adenosine-treated patients cardioverted to sinus rhythm and 77% of these could be directly discharged, accounting for more than half of the patients treated.…”
Section: Electrophysiological Effects Of Adenosinementioning
confidence: 99%